Observations on the Poetics of Erkin Vahidov's Poetry - Kiryigitova, Nigora (FILOLOGIYA UFQLARI JURNALI, 2024)
Erkin Vahidov's poetry, in particular, his ghazals (a genre in poetry) and poems, fell into a period of condemnation and rejection of aruz (a style in lyrics). Perhaps this is why the use of complex words in the work of this particular poet, the ability to turn simple, folk sentences into beautiful poetic lines, has emerged. Nevertheless, Erkin Vahidov was able to create unique examples of poetry without focusing on the beautiful Arabic and gorgeous Persian words. Thus he modernized the old aruz style. However, the same cannot be said of his artistry, that is, his attitude to the means of artistic expression. In other words, Erkin Vahidov did not simplify the traditional arts, but "discovered" their new aspects in the example of his poetry. We study the stylistic devices in the poem "Human" in the lyrics of the poet. Samples of stylistic devices are analyzed in the text of the poem, which reveals the universal, philosophical idea.